Association between glycated hemoglobin variability and risk of diabetic kidney disease and diabetic retinopathy in diabetic patients: a systematic review and meta-analysis - Wu, Chan; Qin, Hanrong; Wei, Maoying; Li, Aijing; Zhu, Qingyi; Guo, Jingyi; Sun, Anning; Gu, Xin; Li, Yincheng; Zhang, Jun; Gong, Yanbing (Frontiers in Endocrinology, 2026)
ObjectiveTo provide a scientific basis for the early prevention of diabetic kidney disease and diabetic retinopathy progression in diabetic patients by systematically evaluating the relationship between glycated hemoglobin (HbA1c) variability and diabetic kidney disease and diabetic retinopathy in these patients.MethodsDatabases including PubMed, Web of Science, Cochrane Library, and Embase were searched for studies investigating the association between HbA1c variability and adverse renal events or retinal diseases in diabetic patients, with data collected from the establishment of each database up to August 5, 2025. Two researchers independently conducted literature screening, data extraction, and assessment of the risk of bias in the included studies. Meta-analysis was performed using the Review Manager 5.3 software, with odds ratio (OR) or hazard ratio (HR) as the effect size indicators.ResultsA total of 45 cohort studies were included in this study, covering 172,111 participants from 20 countries and regions, of which 22 focused on diabetic kidney events and eight on diabetic retinopathy events, and 15 included both outcomes. For the meta-analysis of the association between HbA1c variability and adverse renal events, the standard deviation (SD) of HbA1c was associated with the risk of adverse renal events in patients with type 1 diabetes mellitus (T1DM), with an HR of 0.97 [95% confidence interval (CI): 0.64–1.48, p = 0.90] and an OR of 1.76 (95% CI: 1.12–2.77, p = 0.01); additionally, for each 1% increase in HbA1c-SD, the incidence of adverse renal events in T1DM patients increased, with an HR of 1.40 (95% CI: 1.23–1.59, p< 0.00001). In patients with type 2 diabetes mellitus (T2DM), the coefficient of variation (CV), SD, and high HbA1c variability score (HVS) of HbA1c were all associated with the mortality of adverse renal events, and all HbA1c variability indicators [CV, CV-per 1% increase, SD, SD-per 1% increase, hemoglobin glycation index (HGI), and HVS] were associated with an increased risk of adverse renal events in this population. For the meta-analysis of the association between HbA1c variability and retinopathy, HbA1c-CV was associated with the risk of retinopathy in T1DM patients, with an HR of 1.15 (95% CI: 1.08–1.22, p< 0.0001); HbA1c-SD was also significantly associated with the risk of retinopathy in T1DM, with an HR of 1.83 (95% CI: 1.28–1.63, p = 0.001) and an OR of 4.89 (95% CI: 1.64–14.65, p = 0.005); in T2DM patients, both HbA1c-CV and SD were significantly associated with the risk of retinopathy, with HRs of 1.12 (95% CI: 1.07–1.17, p< 0.00001) and 1.19 (95% CI: 1.06–1.34, p = 0.003), respectively.ConclusionHbA1c variability is positively associated with the risks of adverse renal events and retinal diseases in diabetic patients. Therefore, HbA1c variability may play an important and promising role in guiding blood glucose control targets for diabetic patients and predicting the progression of adverse renal events or retinal diseases.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251133099.